1985
DOI: 10.1182/blood.v66.2.380.bloodjournal662380
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of cytogenetic studies in 100 patients with multiple myeloma, plasma cell leukemia, or amyloidosis

Abstract: Chromosome studies were done on 82 patients with multiple myeloma, 11 with amyloidosis, 2 with multiple myeloma and amyloidosis, and 5 with plasma cell leukemia to investigate their chromosomal abnormalities and to determine the usefulness of cytogenetic studies. A chromosomally abnormal clone was found in 29 patients but was observed most often in those with active disease: in 18% of patients with newly diagnosed multiple myeloma, in 63% with aggressive disease, and in 40% with plasma cell leukemia. Survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…MM is cytogenetically characterized by complex numerical and structural aberrations, none of them being totally specific. Our cytogenetic results in 30 MM patients are also in full agreement with the most consistent cytogenetic findings showing breakpoint clusters on chromosomes 1, 14q32 breakpoint (Ferti et al, 1984;Dewald et al, 1985;Weh et al, 1993) and other abnormalities of B-cell disorders, such as the reciprocal t(11;14)(q13;q32) (Meeus et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…MM is cytogenetically characterized by complex numerical and structural aberrations, none of them being totally specific. Our cytogenetic results in 30 MM patients are also in full agreement with the most consistent cytogenetic findings showing breakpoint clusters on chromosomes 1, 14q32 breakpoint (Ferti et al, 1984;Dewald et al, 1985;Weh et al, 1993) and other abnormalities of B-cell disorders, such as the reciprocal t(11;14)(q13;q32) (Meeus et al, 1995).…”
Section: Discussionsupporting
confidence: 90%
“…The detection of aneuploid malignant PC by flow cytometry and fluorescence in situ hybridization in about 80% of patients (Zandecki et al, 1994;Drach et al, 1995), demonstrated that the 20-60% incidence of karyotypic abnormalities (Dewald et al, 1985;Gould et al, 1988;Gutensohn et al, 1992;Cigudosa et al, 1994;Lai et al, 1995;Sawyer et al, 1995) largely underestimated the frequency of genetic damage in MM (Zandecki et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact has spurred the search for valid prognostic factors. Several prognostic markers have been identified (Dewald et al, 1985;Bataille et al, 1992;Greipp et al, 1993), leading to the proposal of different prognostic systems. Recent studies have introduced serum HGF and serum syndecan-1 as prognostic markers for survival in myeloma patients (Seidel et al, 1998(Seidel et al, , 2000b.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent IgH translocations in MM are t(11;14), involving cyclin D1 and t(4;14), involving FGFR3. The t(11;14) is detectable in 5% of MM patients by conventional cytogenetics (Dewald et al, 1985;Sawyer et al, 1995;Fonseca et al, 1998) and is detected in 15-20% of MM patients by FISH (Konigsberg et al, 2000;Avet-Loiseau et al, 2002;Fonseca et al, 2002). It is thought to be associated with good prognosis (Fonseca et al, 2002(Fonseca et al, , 2003Moreau et al, 2002).…”
mentioning
confidence: 99%